If you traveled on the underground railroad - Levine, Ellen; Williams, Richard (New York : Scholastic, 1988)
Describes the underground railroad which helped slaves escape to freedom.
Keywords: Underground Railroad -- Juvenile literature; Fugitive slaves -- United States -- Juvenile literature; Underground Railroad; Fugitive slaves